2021
DOI: 10.1155/2021/5529032
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Quality of Life in a Sample of Italian Women with a Diagnosis of Fibromyalgia: The Role of Attachment Styles

Abstract: Background. Women with fibromyalgia (FM) commonly suffer from depression, pervasive fatigue, and pain. The attachment style has been hypothesized to be an important factor for understanding the experience of these symptoms. Therefore, the present cross-sectional study is aimed at investigating the effect of attachment styles in women with a diagnosis of FM on depressive symptoms and quality of life. Method. Participants were 453 Italian women with a physician’s diagnosis of FM with a mean age of 47 years ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Such interventions can also be adapted to FM patients with insecure attachment and may help to diminish difficulties in pain perception, perception of illness and seeking social support [27]. Moreover, such psychotherapeutic interventions may also help to overcome depressive symptoms in FM patients, which has been found to be closely related with insecure attachment in this patient group [28]. In this regard Sechi et.…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions can also be adapted to FM patients with insecure attachment and may help to diminish difficulties in pain perception, perception of illness and seeking social support [27]. Moreover, such psychotherapeutic interventions may also help to overcome depressive symptoms in FM patients, which has been found to be closely related with insecure attachment in this patient group [28]. In this regard Sechi et.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was performed by examining the Pearson correlation coefficient (when both distributions were normal) or Spearman's test (when at least one distribution was not normal). It has been confirmed that the stronger the depressive symptoms, the greater the impact of fibromyalgia on the quality of life [ 26 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Rather, it has been hypothesized that IA represents an important predisposing factor to alexithymia which, conversely, has been found to be a predictive personality trait of FMS [66,67]. Regardless, the presence of IA represents an important predictor of lower quality of life in patients with FMS and this effect appears to be mediated by low self-esteem [68] and depressive symtpoms [69]. In other words, the presence of IA (dismissive, preoccupied and fearful), could be responsible for a greater biopsychosocial impact and a higher disease burden in female patients with FMS [68,69].…”
Section: The Relationship Between Bss and The Insecure Attachment In ...mentioning
confidence: 99%